Numerical investigation of rare earth leaching in a stirred tank using a computational fluid dynamics–discrete element method–volume-of-fluid model - E, Dianyu; Wu, Yiliu; Yang, Zhiwei; Wen, Yingming; Sun, Weifu; Chu, Kaiwei; Luo, Diqiang; Ma, Huaqing; Cui, Jiaxin (Physics of fluids (1994), 2025)
Leaching is the core step in rare earth processing, enabling efficient separation of rare earth elements through selective dissolution. It determines resource utilization rates, environmental impact, and the economic viability of subsequent purification processes, underpinning the sustainable, high-efficiency growth of the rare earth industry. It should be widely recognized that the leaching process is inherently complex and subjects to multiple influencing factors. In this paper, the leaching of the rare earths in a stirred tank is selected as the research object, and the primary attention is given to the numerical investigation of the effect of the particle size on the leaching process. To this end, a computational fluid dynamics–discrete element method–volume-of-fluid model is developed to simulate gas–liquid–solid three-phase flows in a stirred tank, incorporating the unreacted shrinking core model to predict the leaching behaviors of the rare earth particles. Based on the simulation results, the effects of on particle flow behaviors, leaching behaviors, and power consumption are subsequently analyzed. The analysis results indicate that it is more recommended to use finer particles due to the more uniform distribution, higher leaching efficiency, lower power consumption, and less fluctuation of the power consumption during the leaching process. This paper should provide the relatively significant reference value for optimizing rare earth leaching process in industrial applications.